Overview of Prince2 (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. PRINCE2 is a type of project management system that puts great emphasis on control. It aims to ensure that a challenging, complex project can be easily managed and controlled by being divided into smaller stages and conducted with certain principles in mind. It's a strategic approach founded on the belief that all projects, no matter how well-planned or high-budget they are, can fall apart due to changes from external forces and a failure to manage risks. With Prince2, you only need to deal with one stage at a time, which provides much more control. In this track, we walk you through the basics of PRINCE2. This track is ideal for anyone looking to take a project management qualification but wants to find out more about PRINCE2. Learning Objectives Learn what the PRINCE2 methodology is, and why it's important Learn what makes PRINCE2 unique Learn why PRINCE2 suits some projects more than others Learn the basics of Prince2.